THE IMPLEMENTATION OF THE MEDINA CONSTITUTION IN MODERN STATE ADMINISTRATION: A THEORETICAL VIEWPOINT - Yusuf Faisal Ali (Asy-Syari'ah, 2021)
Abstract: The presence of the Constitution of Medina that was declared by the Prophet Muhammad after His migration did not only manage and organize the internal life of Muslims and unify them with the Jews as well as their allies but also presented a change on social status from stateless society to state society. It addresses an idea that the substance in the Constitution of Media should be overviewed and seen from various aspects of state’s and nation’s life. The purpose of this research is more intended to analyze the political principles in the Constitution of Medina. This study is qualitative with analytical descriptive method from data obtained in the literature. The data is then collected and analyzed inductively and deductively, which is elaborated with constitutional theory. This study resulted that substantially the Constitution of Medina contained the principle of politics that globally included elements of the state formation, model of state, governmental system, and type of power that remained in-progress at Medina based on the existing literatures in governmental science, political science, and developing countries in the whole world. The main aspect revealed in this study concerns the substance and implementation of the Medina constitution in the state administration that is relevant to modern countries that are developing at this time, both sociologically and politically.Abstrak: Kehadiran konstitusi Madînah yang ditetapkan oleh Nabi Muhammad setelah berhijrah, sesungguhnya tidak hanya sekedar menata intern kehidupan kaum muslimin dan mempersatukan di antara mereka dengan kaum Yahudi beserta sekutu-sekutunya, tetapi juga memberikan perubahan status sosial yang mulanya dari masyarakat bukan negara menjadi masyarakat yang bernegara. Ini memberikan gambaran bahwa materi konstitusi Madînah tidak dapat dilihat dari satu sisi atau dua sisi saja, tetapi mencakup berbagai aspek kehidupan dalam bermasyarakat dan bernegara. Adapun tujuan dari penelitian ini lebih dimaksudkan untuk menganalisis prinsip-prinsip kenegaraan dalam konstitusi tersebut. Kajian ini bersifat kualitatif dengan metode deskriptif analitis dari data yang diperoleh secara literatur. Data tersebut kemudian dihimpun dan dianalisis secara induktif dan deduktif, yang dielaborasi dengan teori ketatanegaraan. Hasil penelusuran menunjukkan bahwa secara subtansial konstitusi Madînah memuat prinsip-prinsip kenegaraan yang secara global meliputi unsur-unsur terbentuknya sebuah negara, bentuk negara, sistem pemerintahan, dan jenis kekuasaan yang berlaku di Madînah pada saat itu sebagaimana yang dikenal dalam kepustakaan Ilmu Negara dan Ilmu Politik, dan juga sebagaimana yang berkembang di negara-negara di dunia. Aspek utama yang terungkap dalam kajian ini menyangkut substansi dan implementasi konstitusi Madînah dalam ketatanegaraan yang relevan dengan negara-negara modern yang berkembang saat ini, baik secara sosiologis maupun politis.